(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The research objective was to examine how to develop a mathematics task book with a Problem Based Learning model to improve the creative thinking of grade VII students. This study developed a mathematics task book with a Problem Based Learning model to improve the creative thinking of grade VII students by using the development model by Plomp and Nieven, where the development stage consists of four stages (preliminary research, prototyping stage, assessment stage (summative evaluation), Systematic reflection and documentation). A mathematics task book with a Problem Based Learning model to improve the creative thinking of seventh grade students will be developed; Mathematical problem solving questions, questions to bring up students’ creative thinking, student assignments, and evaluation. Validation conducted by media validators showed that the overall percentage results performed by media and material expert validators were 95.2%, meaning that the mathematics task book with the Problem Based Learning model to improve creative thinking of grade VII students was included in the very good category (feasible). The results of the completeness test of the learning outcomes of students who were taught using the mathematics task book with the Problem Based Learning model to improve the creative thinking of seventh grade students were better than students who were not taught with the mathematics task book with the Problem Based Learning model to improve the creative thinking of seventh grade students (learning conventional).